Ketergantungan siswa/i MTS menggunakan kalkulator dalam menyelesaikan soal matematika - Yusra, Isna; Putri, Nelliani; Fariha, Maulia (ARKA INSTITUTE, 2022)
Learning psychology in Junior High School contributes to the development of students in learning mathematics, involving behaviour, mindset, and application of science in everyday life. This research applies learning media to the concept of geometry of the spatial plane, specifically linear equations of 2 variables. The aim was to improve students' understanding and measure their dependence on calculators in solving SPLDV problems. The results showed a comparison between the conditions before the provision of learning methods or educational media. Previously, only a few students were familiar with learning about SPLDV. However, after the application of educational media, there was a significant increase in students' understanding of mathematics material, especially regarding linear equations of 2 variables. The implication is that this approach can be the basis for improving mathematics learning at the Junior High School level, reducing dependence on calculators, and having a positive impact on student learning outcomes.